1976
DOI: 10.2320/matertrans1960.17.149
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscope Study on Deformation and Fracture of Cementite in Cold-Rolled Steels

Abstract: In order to study the deformation behavior of cementite in carbon steels cold-rolled to various degrees of reduction, observations of dislocation structures were made by using a transmission electron microscope.The results obtained are summarized as follows:(4) The fracture of lamellar cementite proceeded in the following way: (a) The gliding of cementite crystals in the heterogeneous manner results in division of the original cementite crystal into several undeformed blocks. (b) The mutual gliding displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…This is in agreement with the finding of Keh [58], who identified (010) as the major slip and stacking fault plane of Cm. The same slip geometry has also been observed by Inoue et al [15]. They concluded that dislocation glide along (100), (010) and (001) was connected with plastic deformation of Cm.…”
Section: Discussionsupporting
confidence: 65%
“…This is in agreement with the finding of Keh [58], who identified (010) as the major slip and stacking fault plane of Cm. The same slip geometry has also been observed by Inoue et al [15]. They concluded that dislocation glide along (100), (010) and (001) was connected with plastic deformation of Cm.…”
Section: Discussionsupporting
confidence: 65%
“…Electron microscopy studies by Maurer and Warrington, [5] Gil Sevillano, [6] and Inoue et al [7,8] established that cementite lamellae in pearlite deformed to somewhat lower strains contain numerous planar defects and slip bands. In this study, the drawing process reduces cementite lamellae to a thickness of about 2 to 5 nm and introduces numerous boundaries between the cementite nanocrystals.…”
Section: Discussionmentioning
confidence: 99%
“…The latter appear much like the stacking faults and slip traces seen in pearlitic cementite deformed to low strains. [5][6][7][8] These observations indicate that there is some internal strain in the as-transformed pearlite. Figure 2 shows cross-sectional TEM micrographs of a wire drawn to a true strain of 4.22.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,4) These excellent mechanical properties are considered to come from strengthening of ductile ferrite layers 1,2) and at the same time some amount of stable plastic deformation of brittle cementite layers. 5,6) Dislocations needed for the plastic deformation of cementite layer are supplied from the ferrite layers 7) and the stable plastic deformation of cementite layer is realized when yield stress and strain hardening rate of the ferrite layers are increased. 8) Thickness of ferrite layer decreases with reduction of cross-section area of pearlite wire by drawing.…”
Section: Introductionmentioning
confidence: 99%